A239 AN APPROACH TO GASTRIC BALLOON RETRIEVAL ADMIDST COVID-19 RELATED TRAVEL RESTRICTIONS. (4th March 2021) - Dahiya, M; Tomaszewski, M; Bond, A; Donnellan, F; Mohamed, R
Abstract: Background: Given the COVID-19 pandemic, international travel restrictions have been in effect since March 2020 in Canada. As a result, some patients requiring international travel for medical care have experienced delays. Therefore, innovative techniques were required to provide care that would not routinely be performed in Canada, as in the case of Orbera® gastric balloon retrieval. Aims: To describe an approach to gastric balloon retrieval amidst COVID-19 related travel restrictions Methods: Case review of three cases of gastric balloon retrieval was performed Results: 1: A 41-year-old (yo) woman had an Orbera® gastric balloon placement in Washington state in September 2019. She lost 42lbs. Retrieval was scheduled for March 2020, but was delayed due to COVID-19 restrictions. In May 2020, she developed symptoms of balloon dysfunction. The patient was referred to a Canadian tertiary care centre. Gastroscopy was performed under conscious sedation. The Orbera® balloon was in the distal gastric body. The balloon was punctured with a 19G EUS FNA needle; 600cc of blue tinted liquid was aspirated. The emptied balloon was retrieved successfully using rat tooth forceps. 2: A 35-yo woman had an Orbera® gastric balloon placed in October 2019 in Toronto at a private health facility. She lost 20lbs. Retrieval of the balloon was scheduled for March 2020, but due to COVID-19 restrictions, it was not possible at the original facility. She did not have symptoms related to the balloon. Gastroscopy was performed under general anesthesia (GA) on October 8, 2020. The balloon was intact in the distal gastric body. The balloon was punctured with a 19G Cook Echotip Needle and vacuum suction applied; 400cc of blue tinted fluid was removed. Alligator forceps were used to create holes in the underside of the balloon, allowing excess fluid to be expelled as the balloon was pulled up against the GEJ. Once the balloon was deflated, it was removed successfully through the mouth. 3: A 38-yo man had an Orbera® gastric balloon placed in his native Columbia in March 2020. He did not achieve weight loss. Due to COVID-19 restrictions, he was unable to return for planned removal. He did not have symptoms related to the balloon. Gastroscopy was performed under GA on October 8, 2020. The balloon was intact in the distal gastric body. The balloon was punctured with a 19G Cook Echotip Needle and vacuum suction applied; 600cc of blue tinted fluid was removed. Alligator forceps were used in retroflexion to tear the underside of the flattened balloon to ensure all liquid and air had escaped from the balloon. Once the balloon was deflated, it was removed successfully through the mouth. Conclusions: Although Orbera® gastric balloon retrieval is not routinely performed in Canada, we demonstrate that gastroscopy with balloon puncture and forceps-retrieval is a safe option. Funding Agencies: None